Prevalence, satisfaction and preference of tooth shades and their correlation with age, gender and skin shade: A cross sectional study [version 2; peer review: 1 approved, 2 approved with reservations] - Vignesh Kamath; Ann Sales; Sandipan Mukherjee; Puneeth Hegde; Sharon Saldanha; Mahesh M; Umesh Pai; Shobha Rodrigues; Thilak Shetty; Alisha Ono; Srikant Natarajan; Tanay Chawda; et al. (F1000Research)
Shade selection is one of the most important factors that determines the satisfaction of the patient with the dental prosthesis and thus the overall success of the treatment. Conventional methods of shade selection require the presence of existing teeth or past dental/photographic records. Despite the presence of these records, shade selection continues to be challenging, subjective and arbitrarily based on the patient’s age and gender especially if the visual method is employed. This study aims to assess the prevalence, satisfaction, and preference of tooth shades in a cross section of the local Indian population, investigating their correlation with age, gender, and skin color in a diverse sample of 120 participants visiting the outpatient department of this Institution. Methods A total of 120 participants, 60 males and 60 females, categorized into four age (n=15): groups 20-30, 30-40, 40-50, & 50-60 yrs were recruited randomly and evaluated visually using the VITA 3D Master in the study. Participants were also asked about their satisfaction with existing tooth shades and their preferences. Results The most common existing tooth shade was Value 2 (52.5%). Statistical analysis using Chi-square tests revealed that Value 2 was the most desired shade among males and females alike, particularly in the age group of 41 to 50 years (p < 0.001). Shade 2L1.5 was the most prevalent (n=26), with Value 2 (59.16%) being the most sought-after shade, followed by Shade 2L1.5 (n=21), Shade 2M1 (n=18), Shade 1M1 (n=15), and Shade 2R1.5 (n=14). Existing tooth shades of Value 0 were the least common. The highest satisfaction with existing shades was observed in males aged 41 to 50 (n=15), followed by males aged 51 to 60 (n=14) and females aged 31 to 40 (n=12) and 41 to 50 (n=12). Significant differences in satisfaction were noted among males (p < 0.001). Conclusions This study reveals a consistent and strong preference among both males and females for tooth shades classified as Value 2, following the VITA Tooth-Guide 3D Master shade guide. This universal preference suggests the relevance and acceptance of this shade category across diverse patient groups.